2013
DOI: 10.4049/jimmunol.1202177
|View full text |Cite
|
Sign up to set email alerts
|

A Pathogenic Role for CD4+ T Cells during Chikungunya Virus Infection in Mice

Abstract: Chikungunya virus (CHIKV) is an alphavirus that causes chronic and incapacitating arthralgia in humans. Injury to the joint is believed to occur because of viral and host immune-mediated effects. However, the exact involvement of the different immune mediators in CHIKV-induced pathogenesis is unknown. In this study, we assessed the roles of T cells in primary CHIKV infection, virus replication and dissemination, and virus persistence, as well as in the mediation of disease severity in adult RAG2−/−, CD4−/−, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
277
3
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(333 citation statements)
references
References 51 publications
40
277
3
2
Order By: Relevance
“…Thus, it was of importance to assess the individual merits of new CHIKV vaccine platforms in a more stringent animal model that more closely resembles a clinical setting. Antibody responses are known to correlate with protection against CHIKV (29)(30)(31)(32)(33)(34)(35)(36), but CD4 T cell responses may also be important (37)(38)(39). Thus, it was of importance to determine the potential immunological differences that our vaccine candidate might display.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was of importance to assess the individual merits of new CHIKV vaccine platforms in a more stringent animal model that more closely resembles a clinical setting. Antibody responses are known to correlate with protection against CHIKV (29)(30)(31)(32)(33)(34)(35)(36), but CD4 T cell responses may also be important (37)(38)(39). Thus, it was of importance to determine the potential immunological differences that our vaccine candidate might display.…”
Section: Discussionmentioning
confidence: 99%
“…Disease signs and symptoms following infection with CHIKV have been associated with CHIKV infection of cells in musculoskeletal tissues, such as fibroblasts and osteoblasts, and infiltration of inflammatory cells-consisting predominantly of monocytes, macrophages, natural killer cells, and T cells-in musculoskeletal tissues. Recent works have demonstrated that mice lacking mature T and B cells and mice lacking CD4 + T cells had reduced joint swelling and less severe musculoskeletal tissue injury during the acute stage of CHIKV disease, suggesting a pathogenic role for CD4 + T cells in CHIKV disease [80,81].…”
Section: Immunopathogenesismentioning
confidence: 99%
“…In the infection by Alphavirus, an increase has been found in the activation of T CD4+ lymphocytes 54,71 , which differentiate to Th17 and infiltrate the synovial space, possibly promoting local inflammation 72 .…”
Section: Pathogenesis Of Chikungunya Virus Diseasementioning
confidence: 99%